A new high step‐up DC power supply with modular switched capacitor cells. Issue 5 (11th November 2022) - Kord, Fahimeh; Rezanejad, Mohammad; Sheikholeslami, Abdolreza
Abstract: In this paper, a novel high step‐up direct current (DC)‐DC converter, using switched‐capacitor (SC) cells, is proposed. Upon turning a set of switches in this converter on/off, the capacitors are connected to each other in a circuit configuration, and charged through the source. Then, the capacitors are reconnected in a different configuration by turning the switches off/on, and generate high output voltage. This modular converter is able to produce flexible, high output voltage from low input voltage sources. The proposed converter is accordingly studied and analysed. To verify the operation of the given converter, it is simulated via the MATLAB‐based Simulink software, and an experimental prototype is subsequently implemented on a laboratory scale.